Preliminary in vitro antiplasmodial activity of Aristolochia griffithii and Thalictrum foliolosum DC extracts against malaria parasite Plasmodium falciparum. (December 2016) - Das, N.; Rabha, Bipul; Talukdar, P.; Goswami, Diganta; Dhiman, Sunil
Abstract Background Resistance development in human malaria parasites against commonly used antimalarial drugs has necessitated the scientific exploration of traditionally used antimalarial plants. Plant derivatives have been used for curing malaria historically. The present study involves in vitro evaluation of two medicinally important plantsAristolochia griffithii andThalictrum foliolosum DC used in antimalarial chemotherapy by the tribes of northeast India. Method Chloroform, ethyl acetate and n–butanol extracts ofAristolochia griffithii andThalictrum foliolosum DC were evaluated in vitro against chloroquine sensitive (SS) and chloroquine resistance strains (RS) ofP. falciparum . The tests were conducted following WHO standard method and the inhibition of parasite (IC50 ) was calculated. Results InA. griffithii, the IC50 value for ethyl acetate extracts against SS was 6.2 ± 0.02 μg/ml and found to be lower than chloroform extracts, which exhibited an IC50 value of 14.1 ± 0.1 μg/ml (t = 191.1; p < 0.0001). The IC50 values of both chloroform and ethyl acetate extracts for RS were higher as compared to the SS (p < 0.0001). InT. foliolosum DC the IC50 concentration of chloroform extracts for SS and RS were 0.5 ± 0.0 and 1.1 ± 0.0 μg/ml respectively (t = 54.2; p < 0.0001). Conclusion The present findings, although preliminary, but scientifically demonstrate that identification and isolation of active compounds of these two plant materials and testing against differentPlasmodium species could lead to the development of potential antimalarial drugs for future.